The Online Processing of Causal and Concessive Relations: Comparing Native Speakers of English and German. Issue 7 (9th August 2021) - Blumenthal-Dramé, Alice
ABSTRACT: This article presents a self-paced reading study comparing the online processing of interclausal discourse relations in native speakers of English and German. The study aims to contribute to two overarching questions: First, it puts to the test the so-called causality-by-default hypothesis, which states that causality is a default assumption, whereas concession is less inferable and thus cognitively inherently more complex. Second, it explores the hypothesis that native speakers of English rely more strongly on online inference than native speakers of German. This hypothesis derives from the well-established description of English as exhibiting looser form-function mappings than German. The results of three self-paced reading experiments (one lab-based, two crowdsourced) confirm that readers of German benefit significantly more from the presence of interclausal connectives than readers of English. Moreover, as expected, concessive connectives provide greater processing advantages than causal ones in both languages. Finally, the bias to take causality for granted is only found in English, whereas readers of German do benefit from the presence of causal connectives. It is argued that an account inspired by typological and information-theoretic perspectives is best suited to accommodate these results.